Bulk synthesis of silver-head colloidal rodlike micromotors - Gao, Y; Dullens, R; Aarts, D (Royal Society of Chemistry, 2018)
Colloidal particles with asymmetric catalytic activities are emerging micro/nanomotors that harvest chemical energy for propulsion in fluids. It is of general interest to produce such particles with high performance, in large quantity and at low cost. In this paper, we present a facile bulk method to synthesize silver-head colloidal silica rods. These particles self-propel towards their active sites by reacting with hydrogen peroxide, and the velocity is tuned via the fuel concentration. We show that these motors are highly efficient; compared to the currently available chemical-phoretic micro/nanomotors they show similar performance of self-propulsion at fuel concentrations that are two orders of magnitude smaller.